A Technique for Quality Control and Selection of Tidal Harmonic Constituents - Crawford, William R. (The International Hydrographic Review, 2015)
This paper outlines a procedure to select an optimal set of tidal harmonic constants for use in the prediction of tidal heights. We begin with 18 sets of harmonic constants, each computed from one of 18 consecutive years of hourly tidal heights at a port using a standard tidal analysis program. These constituents are input to a spreadsheet in which are computed average amplitude and phase, and standard deviations of amplitude over the 18 years. As well, graphs of the amplitude and phase deviations for all constituents are presented to allow a user to identify any trend or cyclical variation in the amplitudes or phases, and to identify years where the quality of measurement is poor. The standard error of the average amplitude is computed and may be used as an accept/reject criterion for inclusion of tidal constituents in subsequent predictions. Although nominally intended for 18 years of data, the program will operate on a smaller number of years, and can be adapted to include more years. Many tidal constituents of astronomical origin have frequencies close to or identical with shallow water constituents generated by the interaction of astronomical constituents. If the shallow water constituent interferes with the astronomical one, it will modulate the amplitude and phase of the astronomical constituent, often with periods near 8 and/or 19 years. This modulation can be identified in the time series plots of deviations of amplitudes and phases.